When to be a dear enemy: flexible acoustic relationships of neighbouring skylarks, Alauda arvensis - Briefer, Elodie; Rybak, Fanny; Aubin, Thierry (Animal Behaviour, 2008)
International audience Numerous territorial species are less aggressive towards neighbours than strangers. This tolerance towards neighbouring conspecifics, termed the ‘dear enemy’ effect, seems to be a flexible feature of the relationship between neighbours, and has been shown to disappear in some species after experimental or natural modifications of the context. However, the maintenance over time of this singular relationship has been poorly studied. In this study, we followed the change of dear enemy relationships during the breeding season in a territorial songbird with a complex song, the skylark. We examined in the field the response of territory owners to playbacks of neighbour and stranger songs at three periods of the breeding season, corresponding to three ecological and social situations. Results showed that neighbours were dear enemies in the middle of the season, when territories were stable, but not at the beginning of the breeding season, during settlement and pair formation, nor at the end, when bird density increased owing to the presence of young birds becoming independent. Thus, the dear enemy relationship is not a fixed pattern but a flexible one likely to evolve with social and ecological circumstances.